Membangun Budaya Profesionalitas Pegawai ASN - Saputra Akbar, Wahyu; Frinaldi, Aldri (LPPM Universitas HKBP Nommensen, 2024)
The employee work culture that develops in an organization should continue to improve over time. However, it is currently apparent that the expected productivity is difficult for every employee to maintain. Disregard for moral values and work culture has given rise to several problems in the performance of government institutions, including: (1) Negative opinions from the public regarding public services provided by government officials, (2) Lack of discipline among government officials which affects the quality of services unsatisfactory community, (3) Non-implementation of work culture values which results in negative perceptions of officers, and (4) Lack of knowledge, skills and attitudes among government officers which require improvement. The method used in writing this article is literature study. Efforts to overcome these problems include increasing commitment, supervision, training, implementing incentives, better internal communication, and developing knowledge and skills. By implementing these efforts, it is hoped that public service performance can improve, improve public perception, and build trust in government institutions. The work culture of state officials has a significant impact on the quality of public services. Problems such as negative assessments from society, lack of discipline, non-implementation of work culture values, and lack of knowledge, skills and attitudes affect the effectiveness of services. To overcome this, steps are needed such as increasing commitment, implementing monitoring and incentive systems, socializing work culture values, and developing knowledge and skills.